Regurgitasi Gastroesofageal Bukan Faktor yang mempengaruhi Peningkatan Berat Badan Bayi Usia 0 sampai 6 Bulan: Penelitian Observasional - Yanthi, Dwi; Samsuddin, Samsuddin; Nurjannah, Nurjannah; Rundu, Rundu (Jurnal Stunting Pesisir dan Aplikasinya, 2022)
Regurgitation after breastfeeding, if it occurs excessively for a long time can cause nutritional disorders in infants which prolonged inhibit the growth process. This study aims to identify the incidence of gastroesophageal regurgitation on weight gain in infants aged 0-6 months. The implementation of the study used an observational design, and was located at Puskesmas Lepo-Lepo in September-December 2020. The population was 150 infants, and a total sample of 60 infants as respondents. 88.11% of infants who had regurgitation <3 times per day experienced weight gain, as well as 11.6% who experienced regurgitation 3-5 times per day. The incidence of regurgitation did not affect the baby's weight gain.